2019
DOI: 10.1002/jclp.22796
|View full text |Cite
|
Sign up to set email alerts
|

Affective forecasting and accuracy in social anhedonia: Predicted and experienced emotion for a social interaction

Abstract: Objective Previous research suggests people with social anhedonia (SocAnh) exhibit deficits in anticipated pleasure for social stimuli relative to controls. However, previous research has relied on hypothetical social stimuli and has focused on anticipated pleasure without examining negative affect. Method Participants were informed that they would complete an “enjoyable” sharing task with a peer and were asked to forecast positive and negative affect during the interaction. After the interaction, participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
(97 reference statements)
2
12
0
Order By: Relevance
“…A potential contributor to social deficits in schizotypy involves the reduced positive and greater negative affect observed in response to social stimuli (Statucka & Walder, 2017; Wastler & Lenzenweger, 2018). Lab‐based (Kemp, Gross, Barrantes‐Vidal, & Kwapil, 2018; Moore et al, 2019) and real‐world studies (Chun et al, 2017; Minor et al, 2018) have generally shown that schizotypy is linked with less positive and more negative affect. This may hold important implications for social deficits in schizotypy: when less pleasure or more stress is experienced, there is likely reduced incentive to engage in social activities.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A potential contributor to social deficits in schizotypy involves the reduced positive and greater negative affect observed in response to social stimuli (Statucka & Walder, 2017; Wastler & Lenzenweger, 2018). Lab‐based (Kemp, Gross, Barrantes‐Vidal, & Kwapil, 2018; Moore et al, 2019) and real‐world studies (Chun et al, 2017; Minor et al, 2018) have generally shown that schizotypy is linked with less positive and more negative affect. This may hold important implications for social deficits in schizotypy: when less pleasure or more stress is experienced, there is likely reduced incentive to engage in social activities.…”
Section: Introductionmentioning
confidence: 95%
“…This includes those with schizotypy, a personality framework thought to reflect putative genetic liability for psychotic and other psychiatric disorders (Lenzenweger, 2006; Meehl, 1990). Past studies, mostly occurring in the laboratory with young adults (Dinzeo, Serna, Pujji, & Sledjeski, 2018; Moore, Chan, Huang, & Martin, 2019), show that social functioning deficits are independent of social cognitive and neurocognitive functioning (Aghvinian & Sergi, 2018; McCleery et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While affective forecasting has not been considered in relation to anhedonia generally, there are two recent studies concerned with social anhedonia (SA) which will be briefly mentioned [97 •, 98]. Moore et al [98] reported there were no differences for positive affect; however, those with high SA anticipated and experienced higher negative affect and predicted negative affect more accurately. Zhang et al [97•] reported anticipated valence in social (but not non-social) conditions were associated with connectivity between the retrosplenial cortex and insula, and the hippocampus and parahippocampus.…”
Section: Predicting Future Emotionsmentioning
confidence: 99%
“…Other authors have found that a lack of forecasting errors may be one of the keys to certain disorders. For example, Moore et al (2019) have determined that individuals with social anhedonia, a symptom of schizophrenia and other disorders, are more accurate in forecasting negative affect. Such individuals expect to receive little pleasure from social interactions and do not in fact experience much pleasure during such interactions, potentially leading to increased desire for solitude.…”
Section: The Future Of Predicting the Futurementioning
confidence: 99%